2019
DOI: 10.1002/pd.5463
|View full text |Cite
|
Sign up to set email alerts
|

Digital vs face‐to‐face information provision in patient counselling for prenatal screening: A noninferiority randomized controlled trial

Abstract: Objective To evaluate face‐to‐face information provision in patient counselling for prenatal screening compared with two forms of digital information provision, namely, noninteractive instructional video or interactive video. Method We performed a prospective, noninferiority, cluster‐randomized controlled trial comparing face‐to‐face (usual care) with two forms of digital information provision (intervention) in counselling for prenatal screening. This study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…While it is important to improve pregnant women’s access to prenatal GC, it is paramount that their reported outcomes be considered when implementing alternative GC SDMs. Previous studies have demonstrated the utility of providing digital information on prenatal testing before in-person GC, which was confirmed to help improve patients’ knowledge [ 13 , 21 ], shorten the time required [ 21 ], and reduce decision conflict [ 13 , 16 , 20 ]. Considering our finding that Japanese women tend to prefer in-person GC, such an approach would likely be acceptable in a Japanese population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While it is important to improve pregnant women’s access to prenatal GC, it is paramount that their reported outcomes be considered when implementing alternative GC SDMs. Previous studies have demonstrated the utility of providing digital information on prenatal testing before in-person GC, which was confirmed to help improve patients’ knowledge [ 13 , 21 ], shorten the time required [ 21 ], and reduce decision conflict [ 13 , 16 , 20 ]. Considering our finding that Japanese women tend to prefer in-person GC, such an approach would likely be acceptable in a Japanese population.…”
Section: Discussionmentioning
confidence: 98%
“…While researchers in other countries have explored alternative GC SDMs in the prenatal setting [13][14][15][16][17][18][19][20][21], pregnant women's preferences toward models and durations of pretest GC have been poorly studied. In addition, pregnant women's preferences may vary by country and culture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that both face-to-face and remote counseling increase mothers' awareness of prenatal screening. [ 25 ] Furthermore, when mothers use doctors or nurses as sources of information, the level of anxiety is significantly lower. [ 17 26 ] In the study of Isfahani and Yazdanpanah, it was pointed out that counseling and individual and group education methods are effective in reducing stress and anxiety during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a way to save counseling time and increase patient care. [ 25 ] Amniocentesis is a method of screening for fetal health that causes anxiety in pregnant women, and education can help control the anxiety of pregnant mothers before amniocentesis. The aim of this study was to investigate the effect of education on the anxiety of pregnant mothers before invasive screening for fetal malformations (amniocentesis).…”
Section: Introductionmentioning
confidence: 99%
“…The GCSS was said to be applicable to different genetic counseling practice contexts [ 8 ]. The GCSS has been used to evaluate genetic counseling for melanoma genomic risk [ 22 ], acute intermittent porphyria caused by mutations in the hydroxymethylbilane gene [ 23 ], prenatal genetic counseling [ 24 ], pancreatic cancer with the presence of CDKN2A [ 25 ], Lynch syndrome [ 26 ], coronary heart disease genomic risk [ 27 ], multiple sclerosis [ 28 ], Down syndrome [ 29 ] and breast and ovarian cancers [ 30 ]. However, the fact that the GCSS was deemed to be applicable to different counseling settings does not preclude the requirement to actually validate the scale in all its different usages [ 31 ].…”
Section: Discussionmentioning
confidence: 99%